Racial disparity reform: racial inequality and policy responses in US national politics - Donnelly, Ellen A. (Journal of crime and justice, 2017)
Persistent racial inequality in the US criminal justice system is a significant challenge for policy-makers. Although scholarship has focused on policies that created a punitive criminal justice system and reforms that scale back criminal processing, little is known about policies that elected officials use to address racial issues in criminal justice. This article introduces the framework of ‘racial disparity reform.’ Four types of criminal justice policies that seek to redress politically defined problems of racial inequality are presented. This framework is then used to explain race-targeted criminal justice reforms in US national politics. A qualitative analysis tests how distinct visions of racial inequality prompted US presidents and Congress to initiate a study of race in capital punishment, a ban on racial profiling, and a system-wide corrective to minority overrepresentation in youth confinement. Lessons are drawn concerning the potential of policy-making in forging a more racially egalitarian criminal justice system.